Parental attachment for at-risk children's antisocial behaviour: A case of Malaysia - Siti Hajar, A.B.A.; Haris, A.W.; Islam, M.R. (Taylor & Francis, 2016)
The aim of this study was twofold: to explore the influential factors of parents’ attachment for at-risk children's antisocial behaviour, and to know the types of children's antisocial behaviour caused by being a single-parent family. The sample comprised 1,434 secondary school children from the state of Johore, Malaysia. Results from the structured questionnaire showed that the children were at risk of involvement in antisocial behaviour when their parental controls were either absent or ineffective owing to three risk factors: the absence of parents at home, the number of children in the family, and single-parent family households. The finding of the study has significant policy implications for improvement of parental care to develop child care services in Malaysia.